Da administração legal ao business process management : o mapeamento de processos de negócio em escritórios de advocacia - Agostini, Manuela Rösing (My University, 2014)
This work uses the Legal Administration, as a tool to guide and lead the legal services organizations toward to innovation and competitiveness, along with Business Process Management (BPM) methodology as an option for sustainable competitive advantage. Based on the application of both approaches together, i.e. Legal Administration and BPM, the aim of this research is to identify main business processes that make up the structure of a law firm. A qualitative-exploratory and quantitative-descriptive nature research was realized based on three main phases. The first phase involves identifying criteria and terminological basis within the context analyzed based on the application of three individual semi-structured interviews. After the identification of the terminology dimensions map, the second phase was the application of a structured questionnaire, which was applied on nine Law Firms, certified on ISO 9001, in Brazil. Based on descriptive statistics the main business processes that define the organizational structure of law firms, as well as their supporting processes were identified. The main business process were grouped in four categories and the support business processes were grouped in six categories.
Esse trabalho aborda a Administração Legal como uma ferramenta capaz de orientar e conduzir as organizações prestadoras de serviços jurídicos rumo à inovação e à competitividade, em conjunto com a aplicação da metodologia Business Process Management (BPM) como opção alternativa na busca pela vantagem competitiva sustentável. Alinhando essas duas abordagens, a Administração Legal e o BPM, o objetivo deste trabalho é identificar os principais processos de negócio que compõem a estrutura de um escritório de advocacia. Uma pesquisa de natureza qualitativo-exploratória e quantitativo-descritiva foi realizada, sendo as estratégias metodológicas desenvolvidas em três fases. A primeira fase de coleta de dados envolve a identificação dos critérios e fundamentos terminológicos do contexto analisado, por meio da aplicação de três entrevistas individuais semi-estruturadas. Após a identificação do mapa das dimensões terminológicas, parte-se para a segunda fase da coleta de dados, a aplicação de um questionário estruturado, o qual foi aplicado nos escritórios certificados com a norma ISO 9001 no Brasil. Por meio da estatística descritiva foram identificados os principais processos de negócio que compõem a estrutura dos escritórios de advocacia, bem como seus processos de apoio. Os processos foram agrupados em quatro categorias para os processos principais e em seis categorias para os processos de apoio.
Keywords: Administração; Business process management; Administração legal; Escritórios de advocacia; Business process management; Legal administration; Law firms